Current Measures for the Protection of Atmospheric Air - Uteniyazova Naubakhar Amanbayevna (Genius Journals, 2022)
Winds play an important role in the concentration of pollutants and their movement. A strong wind carries pollutants out of cities, disperses them in large volumes of air. As a result, pollution concentrations decrease. Under certain physical and geographical conditions, strong wind, on the contrary, in some cases leads to an increase in the concentration of dust in the air.
Keywords: Atmosphere; air; waste-free production; dust; gas; strong wind